2021
DOI: 10.1002/aic.17476
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heat‐integrated pressure‐swing azeotropic distillation using a graphical pinch analysis

Abstract: A new graphical method for the fundamental design of pressure‐swing distillation (PSD) and valid heat integration of the designed process is demonstrated based on a pinch analysis. As the minimum pressure constraint, the pinch pressure is determined by this graphical method to secure the necessary temperature driving force and circumvent the distillation boundaries. For a feasibility evaluation of heat‐integrated PSD (HIPSD), the suggested approach requires visualization of the pinch temperature contours and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Conversely, if the feed composition deviates significantly from the azeotropic composition, the process necessitates first directing the feed to a water removal column to obtain a mixture with the composition close to the azeotropic point, before proceeding to the azeotropic distillation column for further separation [9]. Lee et al [10] investigated the separation of isopropanol (IPA), water, and diisopropyl ether (DIPE) through pressure swing distillation. They suggested that for a feed composition of DIPE/IPA/water = 0.36:0.48:0.16, a sequence of a medium-pressure (MP) column, followed by a low-pressure (LP) column, and then a high-pressure (HP) column should be adopted for optimal separation.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, if the feed composition deviates significantly from the azeotropic composition, the process necessitates first directing the feed to a water removal column to obtain a mixture with the composition close to the azeotropic point, before proceeding to the azeotropic distillation column for further separation [9]. Lee et al [10] investigated the separation of isopropanol (IPA), water, and diisopropyl ether (DIPE) through pressure swing distillation. They suggested that for a feed composition of DIPE/IPA/water = 0.36:0.48:0.16, a sequence of a medium-pressure (MP) column, followed by a low-pressure (LP) column, and then a high-pressure (HP) column should be adopted for optimal separation.…”
Section: Introductionmentioning
confidence: 99%